Autistic Symptoms in Schizophrenia: Impact on Internalized Stigma, Well-Being, Clinical and Functional Characteristics - Stefano Barlati; Stefano Barlati; Gabriele Nibbio; Donato Morena; Paolo Cacciani; Paola Corsini; Alessandra Mosca; Giacomo Deste; Vivian Accardo; Vivian Accardo; Valentina Regina; Jacopo Lisoni; et al. (Frontiers in Psychiatry, 2022)
Autism Spectrum Disorders (ASD) symptoms and internalized stigma (or self-stigma) can have a negative impact on cognitive and functional outcomes in people living with schizophrenia. Aim of the present study were to assess and compare internalized stigma, subjective well-being and other socio-demographic, clinical and functional characteristics in people diagnosed with schizophrenia with and without prominent autistic features. Ninety-four inpatients were assessed with measures of internalized stigma, subjective well-being, global clinical severity, schizophrenia symptoms severity, real-world functioning, medication side effects and attitude toward prescribed medications. Subjects with high levels of ASD symptoms were identified with the PANSS Autism Severity Score and compared to other participants. Predictors of prominent ASD features were also assessed. Thirteen patients showed prominent ASD symptoms. They were characterized by fewer years of education, worse real-world functioning and greater symptoms severity. No between-group differences were observed regarding subjective well-being and global internalized stigma severity; however, participants in the “autistic schizophrenia” group showed better stigma resistance. A worse clinical condition and fewer years of education emerged as predictors of autistic schizophrenia. Despite showing a more severe clinical presentation of the disorder and worse functional impairment, participants with prominent ASD symptoms do not present worse subjective well-being or more severe internalized stigma; on the contrary, they show better stigma resistance. ASD symptoms could therefore play a protective role in the internalization of stigma.